Supply Chain Resilience to Mitigate Disruptions: A QFD Approach - Chowdhury, Md. Maruf Hossan; Dewan, Mohammed Naim Ahmed; Quaddus, Mohammed (PACIS, 2012)
With the increase in disruptions and vulnerabilities, demand for more resilient supply chain is echoed vibrantly in business world. It is important to develop resilient capability in right time because supply chain disruptions may be the cause of serious financial loss to the organizations as well as their supply chains. Supply chain managers need to identify supply chain disruptions and vulnerabilities so that they can develop resilience capability corresponding to those disruptions. In this paper, an Analytical Hierarchy Process (AHP) integrated Quality Function Deployment (QFD) technique has been used to identify prioritized vulnerabilities and corresponding resilience capability requirements. Such approach is still absent in the supply chain literature. An illustrative example has also been introduced to get a clear picture of the research process and future research plan.